Studi Korelasional: Status Identitas Vokasional Dan Kesiapan Kerja Siswa SMK Kesehatan Kota Salatiga - Muhammad Nuryanto (IJIP : Indonesian Journal of Islamic Psychology, 2020)
Abstract This study aims to determine the relationship between vocational identity status and work readiness of SMK SMK of Health students in the City of Salatiga. The population in this writing is the SMK of Health students in Salatiga. The sampling technique used was purposive sampling, and the number of samples taken was 80 people. From all SMK of Health in the City of Salatiga, the writer takes 2 classes each from 2 SMK of Health. The data in this study were collected from two questionnaires distributed to our selected sample students, namely the vocational identity status scale totaling 27 items with a reliability coefficient of 0.719, and a work readiness scale of 21 items with a reliability coefficient of 0.803. The result of this research is that there is a strong correlation between vocational identity status and work readiness of Health Vocational School students, the higher the level of students' vocational identity status, the higher their work readiness. The level of significance of the correlation is 0, 556 ( 0.05), indicating that the relationship between the two variables is quite significant. AbstrakPenelitian bertujuan untuk mengetahui hubungan antara status identitas vokasional dengan kesiapan kerja siswa SMK Kesehatan di Kota Salatiga. Populasi dalam penulisan ini adalah siswa SMK Kesehatan di Salatiga. Teknik pengambilan sampel yang digunakan adalah purposive sampling, dan jumlah sampel yang diambil sebanyak 80 orang. Dari keseluruhan SMK Kesehatan di Kota Salatiga, penulis mengambil masing-masing 2 kelas dari 2 SMK Kesehatan. Data pada penelitian kali ini dihimpun dari dua angket yang disebar kepada siswa sample yang telah kita pilih, yakni skala status identitas vokasional berjumlah 27 item dengan koefisien reliabilitas 0,719, serta skala kesiapan kerja berjumlah 21 item dengan koefisien reliabilitas 0,803. Hasil penelitian terdapat hubungan yang cukup kuat antara status identitas vokasional dengan kesiapan kerja siswa SMK Kesehatan, semakin tinggi tingkat status identitas vokasional siswa maka semakin tinggi pula kesiapan kerja mereka. Tingkat signifikansi korelasi adalah 0, 556 ( 0,05), menunjukkan bahwa hubungan antara dua variabel cukup signifikan.